2006
DOI: 10.1071/ar05182
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the excretion rate of endogenous purine derivatives in the urine of Bos indicus and Bos taurus steers

Abstract: Abstract. Estimates of microbial crude protein (MCP) production by ruminants, using a method based on the excretion of purine derivatives in urine, require an estimate of the excretion of endogenous purine derivatives (PD) by the animal. Current methods allocate a single value to all cattle. An experiment was carried out to compare the endogenous PD excretion in Bos taurus and high-content B. indicus (hereafter, B. indicus) cattle. Five Holstein-Friesian (B. taurus) and 5 Brahman (>75% B. indicus) steers (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…The flow of MCP to the intestines of steers was calculated using the equations proposed by Chen and Gomes (1995). These calculations were made using the value for endogenous purine derivative excretion determined for highcontent (>75%) B. indicus cattle by Bowen et al (2006), i.e. 190 mmol/kg W 0.75 .day.…”
Section: Calculationsmentioning
confidence: 99%
“…The flow of MCP to the intestines of steers was calculated using the equations proposed by Chen and Gomes (1995). These calculations were made using the value for endogenous purine derivative excretion determined for highcontent (>75%) B. indicus cattle by Bowen et al (2006), i.e. 190 mmol/kg W 0.75 .day.…”
Section: Calculationsmentioning
confidence: 99%
“…Regarding the effect of genetic groups, Bowen et al (2006) found difference (Po0.001) for endogenous losses of PD 0.414 and 0.1898 mmol/kgPC 0.75 , respectively, in B. taurus and B. indicus fasted for 7 days. However, the same authors did not find difference (P¼ 0.2) for the average excretion of PD during the trial period in which the animals were fed at maintenance.…”
Section: Discussionmentioning
confidence: 85%
“…However, the same authors did not find difference (P¼ 0.2) for the average excretion of PD during the trial period in which the animals were fed at maintenance. Bowen et al (2006) stated that the reason for the low endogenous excretion PD in B. indicus cattle is unclear. Osuji et al (1996) obtained values numerically lower of endogenous losses of DP for crossbred (B. indicus  B. taurus) when compared with Zebu (B. indicus), respectively, 0.108 and 0.172 mmol/kg PC 0.75 for animals fasted for 20 days.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations